Acute hepatitis of unknown aetiology in children: evidence for and against causal relationships with SARS-CoV-2, HAdv and AAV2 - Xin Chen; Abrar Ahmad Chughtai; Chandini Raina MacIntyre; Trisha Greenhalgh; Hisham Ziauddeen; Deepti Gurdasani; Julie McEniery; Aye Moa; Mallory Trent; Emmanuel Mnatzaganian; Stuart Turville; Mohana Priya Kunasekaran (BMJ Paediatrics Open)
Background The cause of acute paediatric hepatitis of unknown aetiology (2022) has not been established despite extensive investigation.Objective To summarise the evidence for and against a causal role for human adenovirus (HAdv), adeno-associated virus 2 (AAV-2) and SARS-CoV-2 in outbreaks of paediatric hepatitis in 2022.Methods We appraised and summarised relevant evidence for each of the Bradford Hill criteria for causality using quantitative (statistical modelling) and qualitative (narrative coherence) approaches. Each team member scored the evidence base for each criterion separately for HAdv, AAV-2 and SARS-CoV-2; differences were resolved by discussion. We additionally examined criteria of strength and temporality by examining the lagged association between SARS-CoV-2 positivity, respiratory HAdv positivity, positive faecal HAdv specimens and excess A&E attendances in 1–4 years for liver conditions in England.Results Assessing criteria using the published literature and our modelling: for HAdv three Bradford Hill criteria (strength, consistency and temporality) were partially met; and five criteria (consistency, coherence, experimental manipulation, analogy and temporality) were minimally met. For AAV-2, the strength of association criterion was fully met, five criteria (consistency, temporality, specificity, biological gradient and plausibility) were partially met and three (coherence, analogy and experimental manipulation) were minimally met. For SARS-CoV-2, five criteria (strength of association, plausibility, temporality, coherence and analogy) were fully met; one (consistency) was partially met and three (specificity, biological gradient and experimental manipulation) were minimally met.Conclusion Based on the Bradford Hill criteria and modelling, HAdv alone is unlikely to be the cause of the recent increase in hepatitis in children. The causal link between SARS-CoV-2, and to a lesser degree AAV-2, appears substantially stronger but remains unproven. Hepatitis is a known complication of multisystem inflammatory syndrome in children following COVID-19, and SARS-CoV-2 has been linked to increased susceptibility to infection post-COVID-19, which may suggest complex causal pathways including a possible interaction with AAV-2 infection/reactivation in hosts that are genetically susceptible or sensitised to infection.